The Eastern Orthodox churches : concise histories with chronological checklists of their primates - Burgess, Michael, 1948- (Jefferson, N.C. : McFarland & Co. Inc., Publishers, 2005)
"Each entry includes a brief summary of the church's history; the location, number, and language of its members; the official title of the primate; the language used in the church; primary sources for the entry; and a chronology of the reigns of the church's primates from its founding to the present day"--Provided by publisher.
Church of Aght'amar -- Church of Aghunie -- Church of Albania -- Coptic Church of Alexandria -- Coptic Catholic Church of Alexandria -- Greek Church of Alexandria -- Latin Church of Alexandria -- Churches of America -- Greek Church of Antioch -- Greek Melkite Catholic Church of Antioch -- Latin Church of Antioch -- Maronite Church of Antioch -- Syrian Catholic Church of Antioch -- Syrian Orthodox "Jacobite" Church of Antioch -- Church of Armenia -- Church of Assyria -- Churches of Austria-Hungary -- Chaldean Church of Babylon -- Church of Belarus -- Church of Bulgaria -- Church of China -- Armenian Apostolic Church of Cilicia -- Armenian Catholic Church of Cilicia -- Armenian Church of Constantinople -- Greek Church of Constantinople -- Latin Church of Constantinople -- Church of Crete -- Church of Cyprus -- Church of Czechoslovakia -- Church of Eritrea -- Church of Estonia -- Church of Ethiopia -- Church of Finland -- Church of Georgia -- Church of Greece -- Churches of India -- Church of Japan -- Armenian Church of Jerusalem -- Greek Church of Jerusalem -- Latin Church of Jerusalem -- Church of Latvia -- Church of Macedonia -- Church of Moldova -- Church of Montenegro -- Church of Poland -- Church of Romania -- Church of Rome -- Church of Russia -- Church of Serbia -- Church of the Sinai -- Churches of Ukraine.
Includes bibliographical references (p. 261-266) and index.
Keywords: Orthodox Eastern Church -- History; Patriarchs and patriarchate -- History; Patriarchs and patriarchate -- Registers